Ultrasonication affects the melatonin and auxin levels and the antioxidant system in potato in vitro - Pesti-Asbóth, Georgina; Molnár-Bíróné, Piroska; Forgács, Ildikó; Remenyik, Judit; Dobránszki, Judit (Frontiers in Plant Science, 2022)
Melatonin is an ancient hormone whose physiological effects have been extensively studied in animals and human. We now know that it also plays a prominent role in the growth and development of plants. In our present experiment, the relationship between endogenous melatonin and the antioxidant system was investigated in potato plant grown in vitro. Changes in redox homeostasis under ultrasound stress were examined. The concentration of small molecule antioxidants and enzymes of the three-level antioxidant pathway was measured. Elisa method was used to determine melatonin levels in plant tissues, at each growth stage (0h, 24 h, 48 h, 1 week and 4 weeks after subculturing the explants) both in control and ultrasound treated plants. Ultrasound stress activated the three-level defense system and decreased endogenous melatonin levels. Melatonin was able to provide protection against membrane damage caused by drastic ultrasound treatment. Melatonin at the heart of the redox network is a key component regulating various biochemical, cellular, and physiological responses. It has a dual role, as it is able to act both as a growth regulator and an antioxidant. A close relationship was evinced between the plant hormone indole-3-acetic acid and melatonin and ascorbic acid.